ANALISIS ALIH KODE DAN CAMPUR KODE BAHASA JAWA DAN BAHASA INDONESIA DALAM INTERAKSI WARGA DESA NAMO BINTANG DUSUN II SUMBERINGIN - Dahnisyah Putri, Dwi; Pulungan, Rosmilan (Universitas Islam Sumatera Utara, 2022)
This study aims to describe the form of code switching and code mixing of Javanese and Indonesian languages in the interaction of residents of NamoBintangDusu II Sumberingin Village. This research is a qualitative descriptive study. The subject of this research is the interaction of the residents of NamoBintang Village. The method of data collection was done by recording, question and answer, and note-taking techniques. The results of the study indicate the cause of the use of Javanese language more often and find out the form of code switching and code mixing conversations which include: internal code switching, external code switching, temporary code switching, and permanent code switching as well as the form of terms in Javanese which include: klotekkan, sengenge , nimble, sluggish, pententengan, and mayeng-mayeng.